FORMULAE FEED FORMULATION SOFTWARE®: A TOOL FOR DIETS FORMULATION - Oliveira, V.; Ceron, M. S.; Rocha, L. T. (Revista Brasileira de Engenharia de Biossistemas, 2019)
This paper describes the development and operation of feed formulation software for different animal species (ruminants and non-ruminants). The software is designed to assist in the training of basic feed formulation skills and is, therefore, a non-commercial software. It is registered in Revista da Propriedade Industrial n° 2525, case BR 51 2019 000953-3, code 730. FORMULAE: Feed Formulation Software® utilizes linear programming to achieve a low-cost solution, respecting imposed by the user. The software is divided into four Submenus: Nutrients, Feed Ingredients and Evaluation, resulting in a user-friendly and intuitive interface that facilitates handling. Outputs can be visualized in the program environment as well as in electronic spreadsheets. The current version allows the user to generate graphs that facilitate the visualization of technical aspects of the feed, helping to understand the results. FORMULAE can be operated in three languages: Portuguese, English, and Spanish. The software provides a user-friendly and intuitive user interface, besides allowing the calculation of balanced diets for animals based on minimal cost.